Use of the Kalina cycle as a bottoming cycle in a geothermal power plant: Case study of the Wayang Windu geothermal power plant. (5th March 2018) - Prananto, Lukman Adi; Zaini, Ilman Nuran; Mahendranata, Bobby Irawan; Juangsa, Firman Bagja; Aziz, Muhammad; Soelaiman, Tubagus Ahmad Fauzi
Highlights: Utilization of waste geothermal brine for power generation. Kalina cycle system 11 (KCS 11) is adopted in the proposed plant. Water-Ammonia ratio and pinch temperature are examined for optimization. Basic properties of heat exchangers is defined to investigate the practicality. The proposed plant delivers 1660.30 kW with thermal efficiency of 13.20%. Abstract: This study focuses on the use of brine discharged from geothermal fluid at the Wayang Windu geothermal power plant. The Kalina cycle system (KCS) is investigated in an effort to generate electricity from the unused brine. This scheme develops KCS 11 owing to good performance at low to mid-range temperatures. Owing to impurities and the SiO2 content in brine, the brine temperature at the outlet of the evaporator is maintained higher than the minimum silica saturation index standard. The ideal performance of the system is obtained with the optimization of the ammonia–water mixture and pinch temperature of the heat exchangers. Moreover, heat exchanger utilities (i.e., evaporators and recuperators) are designed in detail to analyze the feasibility of the system. An air-cooled condenser is adopted in the system owing the remote location surrounded by mountains. The designed system generates 1660.30 kW of electricity with thermal efficiency of 13.20%. Considering the zero cost of brine, this system is expected to be the solution for optimizing electricity generation in Indonesia.